Serotype distribution of invasive and non-invasive pneumococcal disease in children ≤5 years of age following the introduction of 10- and 13-valent pneumococcal conjugate vaccines in infant national immunization programs: a systematic literature review - Izurieta, Patricia; AbdelGhany, Mohammad; Borys, Dorota (Frontiers in Public Health, 2025)
IntroductionWidespread implementation of pneumococcal conjugate vaccines (PCVs)—namely the 7-valent PCV (PCV7), 10-valent pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine (PHiD-CV), and 13-valent PCV (PCV13)—in infant national immunization programs has reduced pneumococcal diseases in children, including invasive pneumococcal disease (IPD), acute otitis media (AOM), and community-acquired pneumonia (CAP). However, as the use of PCV impacts pneumococcal epidemiology, identifying the serotypes associated with remaining disease is crucial to guide future vaccination strategies for this population.MethodsWe systematically searched the literature for observational studies (2006–2020) on pneumococcal serotype distribution in IPD, AOM, and CAP among ≤5-year-old children post-PCV introduction. Serotype-specific pooled percentage averages were calculated by post-PCV period (post-PCV7 or pooled post-PHiD-CV/PCV13), or by PCV product (PHiD-CV or PCV13) to determine the contribution of each serotype to a certain clinical manifestation.ResultsOur analysis of 86 studies (47 on IPD, 30 on AOM, and 9 on CAP) shows continued reporting of several vaccine serotypes in all clinical manifestations post-PHiD-CV/PCV13, particularly serotypes 19A, 3, and 1. In PCV13 settings, serotype 19A reporting was reduced but still prevalent compared to PHiD-CV settings. Predominant non-PCV13 serotypes varied by clinical manifestation.ConclusionPost-PCV implementation, pneumococcal epidemiology in children is intricate. The persistence of some vaccine serotypes, variations across clinical manifestations, rising antimicrobial resistance, and other factors highlight the need for new vaccine technologies providing enhanced and broader protection to children.